Crowdsourcing markets birds of a feather buy together - Libert, Barry (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from We are smarter than me: How to unleash the power of crowds in your business (9780132244794) by Barry Libert and Jon Spector. Our focus here is on the role of communities in manufacturing companies' products or content. The advantages over traditional business models are huge. At iStock, for instance, contributors create the product, deliver it in market-ready format, and even list it in the appropriate category. With little inventory expense or traditional overhead, iStock can price its product far below conventional competitors"--Resource description page.